2018
DOI: 10.1186/s12884-018-1817-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ferric carboxymaltose versus ferrous sulfate for iron deficiency anemia during pregnancy: subgroup analysis of Korean women

Abstract: BackgroundWe performed a post-hoc subgroup analysis in Korean women who participated in the Phase III FER-ASAP (FERric carboxymaltose-Assessment of SAfety and efficacy in Pregnancy) study to compare the efficacy and safety of ferric carboxymaltose (FCM) with oral ferrous sulfate (FS).MethodsPregnant Korean women (gestational weeks 16–33) with iron-deficiency anemia (IDA) were randomized 1:1 to FCM (n = 46; 1000–1500 mg iron) or FS (n = 44; 200 mg iron/day) group for 12 weeks. The primary objective was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 24 publications
3
32
0
2
Order By: Relevance
“…Within the literature reviewed, 13 of the 19 Level I and 4 of the 10 Level II studies did not report a definition of hypophosphatemia. 9,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Methodologies for serum phosphate measurement and clinical definition of hypophosphatemia varied within and across Level I and Level II studies. Of the 19 Level I studies, 15 did not explicitly report the methodology or timing of serum phosphate measurement.…”
Section: Definitions and Reporting Of Hypophosphatemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Within the literature reviewed, 13 of the 19 Level I and 4 of the 10 Level II studies did not report a definition of hypophosphatemia. 9,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Methodologies for serum phosphate measurement and clinical definition of hypophosphatemia varied within and across Level I and Level II studies. Of the 19 Level I studies, 15 did not explicitly report the methodology or timing of serum phosphate measurement.…”
Section: Definitions and Reporting Of Hypophosphatemiamentioning
confidence: 99%
“…Ten observational, retrospective, or post hoc studies were identified as a supplemental data source to RCT articles (Figure 4). 17,[35][36][37][38]42,[46][47][48][49] All ten studies investigated FCM; two also reported on iron sucrose treatment arms. 17,38 Level II studies reported hypophosphatemia rates ranging 0.0-82.0% with FCM and 0.0-22.0% with iron sucrose.…”
Section: Level II Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In a study that assessed efficacy and safety of IV FCM versus oral ferrous sulfate (FS), FCM achieved Hb increase of >2 g/dL in 7 days and >3 g/dL in 2 to 4 weeks [14]. Another study comparing the efficacy and safety of IV FCM versus oral FS in pregnant Korean women (gestational weeks: 16–33) with IDA showed that FCM provided significantly greater improvements in iron parameters and quality of life (QoL) than FS [15].…”
Section: Resultsmentioning
confidence: 99%
“…[ 3 , 6 , 7 ] More than 20 randomized studies revealed that IV administration of iron offers better tolerability, efficacy, and effectiveness than oral iron therapy. [ 8 , 9 ] One randomized control trial reported that the cost of IV use does not exceed that of oral therapy, whereas IV use is more beneficial in terms of superior tolerance and effectiveness. [ 10 ] The adverse effects of iron infusion are major anaphylactic (rare), and less severe or minor reactions such as urticaria, dizziness, facial flushing, arthralgia, myalgia, dysgeusia etc.…”
mentioning
confidence: 99%